Retraction: Mutual effect of Cs(i) and Sr(ii) sorption on nano-talc investigated by EXAFS, modeling and theoretical calculations. Issue 5 (23rd April 2020) - Sun, Yubing; Song, Wencheng; Liu, Yang; Hayat, Tasawar; Alsaedi, Ahmed; Ai, Yuejie; Sharma, Virender K.; Wang, Xiangke
Abstract : Retraction of 'Mutual effect of Cs(i ) and Sr(ii ) sorption on nano-talc investigated by EXAFS, modeling and theoretical calculations' by Yubing Sun et al., Environ. Sci.: Nano, 2019, 6, 672–683.